STUDI KASUS PENGARUH INDIKATOR TERHADAP KEBERLANJUTAN ENERGI DI PROVINSI RIAU - Fuad, Ahsanul; Lisapaly, Leonardy (AUSTENIT, 2024)
Scientific information based on energy sustainability is very important in improving energy sustainability in the future. In this case, the sustainability targets and decision-making issues must be precise, so appropriate, effective, and relevant new indicators are needed to achieve the goal of improving and enhancing energy sustainability infrastructure and are the main objective of this research. Seven indicators were selected for in-depth research from relevant data, and then each indicator was aggregated and analyzed using correlation analysis. The results of the conceptual analysis show that planning must be careful to implement policies by considering the balance of the economy, security of energy supply, and preservation of environmental functions. As a result, the principle of environmentally friendly energy should be a top priority in the future development of sustainable energy.